State Relations, Media, and the Power of Civil Society after the fall of The New Order Regime in Indonesia - Nuruddin Hady; Mohd Hairy Bin Ibrahim (The Journal of Society and Media, 2023)
The role of civil society power in the history of reform in Indonesia cannot be underestimated because the economic crisis did not solely cause the fall of Suharto's New Order regime. Still, the role of civil society forces was very large and well consolidated. This study used qualitative research. The theory used is the theory of power relations. The results of the study found that in the era of Soeharto's New Order, the relationship between the state and civil society was still not seen to play its role; it can even be said that the existence of civil society was very weak and weakened by the regime, although at the end of the New Order, civil society was well consolidated which eventually gave birth to the reform movement and was able to overthrow Suharto's regime. The results also found that, after the reformation in Indonesia, the civil society movement experienced a golden age at the beginning of the reform because the position of civil society was quite strong and well consolidated in overseeing the course of the democratic system. However, in recent years civil society movements have stagnated and even seem weakened because they are in the circle of power.